Plant Hormones Under Challenging Environmental Factors 2016
DOI: 10.1007/978-94-017-7758-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Phytohormones for Abiotic Stress Tolerance in Crop Plants

Abstract: Abiotic stresses including salinity, drought, extreme temperatures, and heavy metals are posing serious threats to agricultural yields as well as the quality of produce. This necessitates the production of cultivars capable to withstand the harsh environmental conditions without substantial yield losses. Owing to the complexity underlying stress tolerance traits, conventional breeding techniques have met with limited success and demand effective supplements to feed the growing food demands worldwide. This nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…Despite the fact that there are not as many of these reports, a thorough review of them has been done and is reviewed here (Khan et al, 2020). BRs control the regulation of photosynthesis, root extension, stomatal growth, leaf senescence, chlorophyll breakdown, and nutritional balance (Daszkowska-Golec, 2011;Kumar et al, 2016). It is well known that BRs play a critical role in how effectively plants can withstand stress and acclimatize to it.…”
Section: Impact Of Stressors On Horticultural Cropsmentioning
confidence: 99%
“…Despite the fact that there are not as many of these reports, a thorough review of them has been done and is reviewed here (Khan et al, 2020). BRs control the regulation of photosynthesis, root extension, stomatal growth, leaf senescence, chlorophyll breakdown, and nutritional balance (Daszkowska-Golec, 2011;Kumar et al, 2016). It is well known that BRs play a critical role in how effectively plants can withstand stress and acclimatize to it.…”
Section: Impact Of Stressors On Horticultural Cropsmentioning
confidence: 99%
“…Phytohormones serve as key signals for the plants to respond to environmental stimuli (Wania et al, 2016). In order to investigate whether BrAGPs were involved in phytohormone responses, we chose 15 classical AGPs, 13 AG peptides and two lys-rich AGPs, which according to our qRT-PCR displayed expression in the leaf.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the expression of each BrAGP gene by exogenous ABA treatment indicates that the AGPs may participate in the signaling cascade by the dynamic release and uptake of glycosyl radicals. It was clear that there is complex cross-talk among plant hormones, which are important in plant growth regulation and defense responses (Kohli et al, 2013; Wania et al, 2016). In this study, we have shown that there is a large overlap of the BrAGPs induced or suppressed by ABA, GA, and MeJA treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Plant endogenous hormones govern these changes, such as the cell membrane composition and morpho-physiological modification [28]. BRs are directly and indirectly involved in resistance against abiotic stress by inducing different molecular changes such as higher photosynthetic efficiency [29,30], the overexpression and maintenance of stress-responsive genes [31,32], osmoprotectant accumulation, and antioxidant enzyme induction [33,34]. Furthermore, phytohormones combat the stress against heavy metals such as soil acidity [35], heat stress [36], and drought stress [28], by inducing different stress-responsive genes.…”
Section: Introductionmentioning
confidence: 99%